2021
DOI: 10.1016/j.molp.2021.06.028
|View full text |Cite|
|
Sign up to set email alerts
|

Plant cytochrome P450 plasticity and evolution

Abstract: The superfamily of cytochrome P450 (CYP) enzymes plays key roles in plant evolution and metabolic diversification. This review provides a status on the CYP landscape within green algae and land plants. The 11 conserved CYP clans known from vascular plants are all present in green algae and several green algaespecific clans are recognized. Clan 71, 72, and 85 remain the largest CYP clans and include many taxaspecific CYP (sub)families reflecting emergence of linage-specific pathways. Molecular features and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(147 citation statements)
references
References 214 publications
(242 reference statements)
3
144
0
Order By: Relevance
“…Plant cells possess numerous enzymatic systems for the generation of different ROS and RONS species [ 122 , 149 , 150 , 151 , 152 ]. These activities comprise an inherent part of the normal metabolism, and the presence of ROS sensing mechanisms determines the key role of ROS in the response of plants to physiological and environmental stimuli through highly complex signal transduction processes [ 35 , 151 ].…”
Section: The Mechanisms Of Ntp Effects On Seed Germinationmentioning
confidence: 99%
“…Plant cells possess numerous enzymatic systems for the generation of different ROS and RONS species [ 122 , 149 , 150 , 151 , 152 ]. These activities comprise an inherent part of the normal metabolism, and the presence of ROS sensing mechanisms determines the key role of ROS in the response of plants to physiological and environmental stimuli through highly complex signal transduction processes [ 35 , 151 ].…”
Section: The Mechanisms Of Ntp Effects On Seed Germinationmentioning
confidence: 99%
“…CYPs can be divided into many subfamilies, and CYPs belonging to the same subfamilies have the same catalytic functions in organisms. The CYPs are mainly composed of single-family clans and multiple-family clans based on phylogenetic classification [3]. The CYP72A gene subfamily, an important component of the multiple-family clan in CYPs, catalyzes numerous crucial reactions in the biosynthesis pathway of many specialized metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…HDZ IV transcription factors may play crucial roles in plant responses to biotic stresses by regulating specific substrates [ 51 ]. We also found that XM_030630414.1, XM_030634601.1 and XM_030649628.1 were predicted to be involved in flower development [ 52 , 53 ]. Interestingly, a putative transcription factor, bHLH63, may be regulated by a specific HDZ IV transcription factor.…”
Section: Resultsmentioning
confidence: 99%